Pemodelan Penurunan Pondasi Struktur Bangunan di Tanah Lunak Kota Banjarmasin Menggunakan Ansys - Darmansyah Tjitradi; Eliatun Eliatun; Oktafianus Steven Tjitradi (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2021)
The soil in Banjarmasin City is of soft clay type having a very low bearing capacity. Hence, it is normal for buildings in this area to have gelam wooden piles as part of the foundation. Foundations based on gelam wooden piles rely on friction which results in the building experiencing differential settlement, tilt, and cracks on the structural elements. This foundation settlement will be modeled using ANSYS software involving fifteen building structural models with brick walls under loads according to SNI 1727:2013 and due to settlement at the support. The modeling aims at understanding the effects of using tie beams on the pattern of structural damage in buildings that experience differential settlement on soft soil. Hasil penelitian menunjukkan bahwa penggunaan tie beam pada pondasi pada tanah lunak berpengaruh terhadap pola kerusakan. Pada tanah keras, ini tidak membawa efek seperti itu tetapi sebaliknya, itu meningkatkan tingkat ketidaktentuan statis struktur. Dalam kasus portal bentang tunggal, pola retakan menyerupai huruf